Œuvres composites / œuvres vivantes ? - Samuel Quenault (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The use of living elements as part of the structure of artworks is especially frequent in the permanent collection of the château d’Oiron, as well as in work made for the temporary exhibitions. This has led us to focus our research on the methods and techniques used for the présentation and conservation of such work. We specifically look at Claire Morgan’s, Here is the End of All Things ; Michel Blazy’s installation Jardin Volant in the 2003 exhibition, the maintenance of Trichoptères by Hubert Duprat, thee replacement of elements of Guiseppe Penone’s Muta.